Global Transcriptomic Profile of Dorsal Root Ganglion and Physiological Correlates of Cisplatin-Induced Peripheral Neuropathy. Issue 2 (March 2019) - Lessans, Sherrie; Lassiter, Cameron B.; Carozzi, Valentina; Heindel, Patrick; Semperboni, Sara; Oggioni, Norberto; Chiorazzi, Alessia; Thompson, Carleveva; Wagner, Monica; Holden, Janean; Rahn, Elizabeth; Sweatt, J. David; et al.
Abstract : Background: Multiple cell signaling pathways are implicated in the development, progression, and persistence of cisplatin-induced peripheral neuropathy. Although advances have been made in terms of understanding specific neurotoxic mechanisms, there are few predictive factors identified that can help inform the clinician approach to symptom prevention or management. Objective: We investigate the differential sensitivity to cisplatin-induced peripheral neuropathy and examine the contribution of dorsal root ganglion (DRG) transcriptional profiles across two inbred strains of mice. Methods: Cisplatin (4 mg/kg intraperitoneal or vehicle control) was administered twice a week for 4 weeks to adult female C57BL/6J and A/J mice—the C57BL/6J strain of mice characterized by a robust mechanical allodynia and the A/J with a mild largely resistant allodynia phenotype. Peripheral nerve conduction velocities (NCVs), electrophysiological evaluation of wide dynamic range (WDR) neurons, morphological examination of DRG neurons, and microarray analysis of spinal cord tissues were compared across the 4 weeks. Results: The A/J strain presents with an early, mild nocifensive response to cisplatin with reduced neuronal activity in WDR neurons and small changes in cross-sectional nucleus size in DRG neurons at 4 weeks. The more nocifensive-sensitive C57BL/6J strain presents with no early changes in WDR neuron responsiveness; however, there were significant changes in DRG size. Both strains demonstrate a drop in NCV after 4 weeks of treatment, with the greatest reduction present in the A/J strain. Transcriptome data implicate neuroimmune modulation in the differential response to cisplatin in the DRGs of A/J and C57BL/6J mice. Discussion: Nocifensive responses in both strains implicate involvement of small myelinated and unmyelinated fibers in neurotoxic cisplatin response, whereas reductions in NCV reflect involvement of the largest myelinated fibers in the peripheral nerves. Microarray data analysis identifies neuropathy-relevant gene sets with differential activation of pathways, suggesting a role for antigen presentation in the differential neurotoxic response to cisplatin across strains. Further research is indicated to determine the relative contributions of each of these potential pathological mechanisms to both the neurotoxic response to cisplatin and to the potential for targeted therapy. Abstract : Supplemental digital content is available in the text.